Development of Interest to Music-Performing Activity through the Interaction of a Teacher and a Student - Vovk, Valentyn; Yarova, Maryna (Pedagogical Discourse, 2015)
The article deals with psychological and pedagogical nature of development interest in music-performing activity through the interaction of the teacher and the student. Spiritual closeness between teacher and student is shifting of the emphasis from the formal-pedagogical to personal relationships, which are very important factor, determining the the results of the educational process. Respect to the personality of the student means special respect for him or her, recognition of the uniqueness of his or her capabilities, interest in him or her, desire to understand, to help and so on. Manifestation of respect is courtesy, communication culture, justice, sincerity, compassion, sympathy, empathy, tolerance etc. Positive interaction, which relies on the emotional potential of the subjects of the educational process, allows accumulating cognitive activity of students, significantly increasing the level of motivation of learning and effectiveness of the educational process in general.